Priprava tankoplastnih vzorcev za presevno elektronsko mikroskopijo - Čekada, Miha (Vakuumist, 2001)
The procedure for specimen preparation for thin film analysis by transmission electron is described. In the first part the mechanical procedure (thinning) is given for classical as well as cross-section transmission electron microscopy. In the second part insight on ionic etching is given including a physical background of the parameters choice.
Keywords: tanke plasti; elektronska mikroskopija; priprava vzorcev; ionsko jedkanje